CASE OF COMPLETE ALBINISM IN MARINE CAT FISH ARIUS CAELATVS (VALENCIENNES) - Pillai, S Krishna; Somvanshi, V S (Indian Journal of Fisheries, 2011)
Complete albinism in the marine cat fish, Ariiis caelaiiis (Val.) is reported for the first time.